Association Between High-density Lipoprotein Cholesterol and Renal Function in Elderly Hypertension. Issue 14 (April 2015) - Zhang, Ya-Ping; Lu, Ming-Gen; Duan, Dayue Darrel; Liu, Ying-Long; Liu, Meilin; Li, Ying; Kuang, Ze-Min; Lu, Yao; Liu, Xing; Li, Xiao-Hui; Yuan, Hong; Ford., Cassandra
<x xml:space="preserve">Abstract</x> Abstract Few studies have yet investigated the possible association between high-density lipoprotein cholesterol (HDL-C) and kidney function in elderly patients with primary hypertension. Accordingly, the aim of the present study was to evaluate the relationship between HDL-C and kidney function in elderly hypertension. A total of 14, 644 elderly hypertensive subjects were enrolled in our cross-sectional study. The patients were categorized based on serum HDL-C level and glomerular filtration rate (GFR) value, respectively. One-way analysis of variance was used to compare the parameters among different groups. Bonferroni correction was performed for multiple comparisons. Analysis of covariance was used to control for confounding factors. The significance of difference between 3 groups and more was determined by chi-square test for categorical variables. Serum creatinine and uric acid were negatively related to HDL-C level, whereas GFR was positively related to HDL-C level in elderly hypertensive patients according to tertiles of HDL-C and tertiles of HDL-C/total cholesterol ratio (all P for trends <0.05). The male elderly hypertensive patients showed stronger relationship between HDL-C and renal function than the female elderly hypertensive subjects. Low HDL-C was associated with renal insufficiency and proteinuria in the hypertensive elderly (P < 0.05). The elderly "renal-hyperfiltrator" appeared to have lower HDL-C level, compared with the "normal renal-filtrator" (P < 0.05). There was an inverse "V" shape between HDL-C and GFR by GFR strata. Our results point out that there is an association of low HDL-C level with impaired kidney function in elderly hypertensive patients. Glomerular hyperfiltration may also affect HDL-C level and sex might be an influential factor for the association of HDL-C with kidney function in elderly hypertension.